Estudo da inter-sazonalidade dos fluxos de calor latente e sensível no Cerrado e Pantanal de Mato Grosso - Curado, Leone Francisco Amorim (2013)
In recent years has intensified the environmental research in the Cerrado and Pantanal regions in order to understand the interrelationships micrometeorological these biomes. This study set out to study the inter-seasonal flows of latent and sensible heat in the Cerrado and the Pantanal of Mato Grosso. Such fluxes were estimated from the Bowen ratio method following the correction of Perez et al. (1999 and 2008) were made and analysis of seasonal and inter-seasonal of latent and sensible heat fluxes from the Bootstrap resampling technique and did the analysis of the relationships between energy flows and system variables through the Pearson correlation. According to the results, the flow of latent and sensible heat present in seasonal differences (between rainy and dry seasons) and inter-seasonal (between the rainy and dry with wet and dry seasons in different years) in virtually all periods . As for interrelations, the fluxes of latent and sensible exhibit complex behavior influencing and being influenced by a group of up to 8 variables among these variables have: the emission of energy by the atmosphere and the clearness index variables that are external to micrometeorology, indicating that there is an influence of micrometeorological and macrometeorológical phenomena the dynamics of the region.